The Nexus between Economic Growth and Natural Resource Abundance in Selected ASEAN countries before Pandemic Covid-19 - Ridzuan, Abdul Rahim; Shaari, Mohd Shahidan; Rosli, Anita; Jamil, Abdul Rahim Md; Siswantini, Siswantini; Lestari, Arsiyanti; Zakaria, Shahsuzan (International Journal of Energy Economics and Policy, 2021)
Abundant natural resources play an important role in boosting economic growth. However, as the Dutch disease emerged in the 1970s, innumerable researchers were attracted to investigate the negative impact of abundant natural resources on economic growth. The issue has been rigorously discussed in a large number of previous studies. However, they did not investigate the effect of economic growth on natural resource abundance. Therefore, this study embarks on an investigation into the effect of economic growth on natural resource abundance in selected ASEAN countries, namely Thailand, Singapore, Malaysia, Brunei, the Philippines, Vietnam, Cambodia and Indonesia. This study employs the static panel method to analyse data ranging from 2000 to 2016. The results show that foreign direct investment and direct investment can have negative impacts on natural resource abundance. An increase in economic growth, on the other hand, can have a positive impact of natural resource abundance. Other factors such as financial development, trade openness and governance do not influence natural resource abundance. Therefore, these findings can shed light for policymakers to formulate policies for future references as the outcomes based on before the spread of Covid-19 diseases. The countries can enhance economic growth to pave the way for more exploration of natural resources. Higher economic growth can lead to more advanced technologies and thus it is easy to extract more natural resources. Foreign direct investment and direct investment should be controlled to ensure that natural resources will not be exhausted. Keywords: natural resource abundance; economic growth; static panel; ASEAN JEL Classifications: O13, Q32, Q33, Q38, Q56 DOI: https://doi.org/10.32479/ijeep.10615